Come fa la voce? Per un’archeologia dell’attore performer (Materiali di Estetica. Terza serie, 2017)
This essay suggests a working hypothesis on the extralinguistic dimension of the human voice. The material under consideration belongs both to performance art (Marina Abramović) and to philosophy (Plato). The speech, framed within a context that would open an archaeological track (E. Melandri, M. Focault) in theatricality, concerns aesthetics. The voice shows the inner opacity of the ontological discourse: it becomes the empty place, or rather, the quantum vacuum of presence. It is a non-prescriptive voice, excessive of the philosophical practices of taking consciousness, the anticipation of traditional dualisms (subject / object, conscious / unconscious, orality / writing).